2007
DOI: 10.1111/j.1439-0310.2006.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Communal Nesting in Asocial Abert's Squirrels: the Role of Social Thermoregulation and Breeding Strategy

Abstract: The social thermoregulation hypothesis states that endothermic species will communally nest to reduce energy expenditures on thermoregulation. The hypothesis predicts that the frequency of communal nesting should increase with decreasing ambient temperature. The potential costs of communal nesting (e.g., increased predation risk, resource competition, cuckoldry, parasite/disease transmission, or infanticide) could decrease the frequency of communal nesting especially for asocial breeding females with dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 43 publications
2
17
2
Order By: Relevance
“…Our observation that social groups were larger at Rinconada than Los Molles suggests that social group formation and maintenance is not driven by social thermoregulation. These findings depart from studies of single populations or comparisons of multiple populations in mammals (mostly rodents) where the extent of grouping tracks changes in ambient temperature (West 1977; Madison 1984; Stapp et al 1991; Edelman and Koprowski 2007; Taraborelli and Moreno 2009). However, our results are in agreement with studies on voles (Getz and McGuire 1997) and badgers (Johnson et al 2002) in which group size is uncoupled from ambient temperatures.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Our observation that social groups were larger at Rinconada than Los Molles suggests that social group formation and maintenance is not driven by social thermoregulation. These findings depart from studies of single populations or comparisons of multiple populations in mammals (mostly rodents) where the extent of grouping tracks changes in ambient temperature (West 1977; Madison 1984; Stapp et al 1991; Edelman and Koprowski 2007; Taraborelli and Moreno 2009). However, our results are in agreement with studies on voles (Getz and McGuire 1997) and badgers (Johnson et al 2002) in which group size is uncoupled from ambient temperatures.…”
Section: Discussioncontrasting
confidence: 87%
“…Johnson et al (2002) found no relationship between the thermal environment (a main determinant of energy expenditure) and the size of social groups across populations of badgers ( Meles meles ) throughout Europe. While these findings contrast with studies of single populations in rodents where the extent of grouping tracks changes in ambient temperature (West 1977; Stapp et al 1991; Edelman and Koprowski 2007), they support other studies (e.g., Getz and McGuire 1997), suggesting that social group size is not influenced by fluctuations in ambient temperature. Regarding reduced costs of burrow construction, burrow digging has been associated to the evolution of sociality across neotropical (Ebensperger and Cofré 2001; Ebensperger and Blumstein 2006) and African hystricognath rodents (Jarvis et al 1994).…”
Section: Introductioncontrasting
confidence: 56%
“…Huddling has been reported as a mechanism to save energy in small eutherian mammals such as Darwin's leaf-eared mouse ( Phyllotis darwini ) (Bustamante et al, 2002), the Alpine marmot ( Marmota marmot ) (Arnold, 1988), Abert's squirrel ( Sciurus aberti ) (Edelman and Koprowski, 2007), the striped mouse ( Rhabdomys pumilio ) (Schradin et al, 2006), the Indiana bat ( Myotis sodalist ) (Boyles et al, 2008), the Cape ground squirrel ( Xerus inauris ) (Wilson et al, 2010), and the neotropical bat ( Noctilio albiventris ) (Roverud and Chappell, 1991). Such behavior is also observed among some Australian marsupials, such as brush-tailed phascogales ( Phascogale tapoatafa ) (Rhind, 2003), eastern pygmy possums ( Cercartetus nanus ) (Namekata and Geiser, 2009), and sugar gliders ( Petaurus breviceps ) (Quin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The social thermoregulatory hypothesis states that animals will huddle to reduce 158 energetic costs associated with thermoregulation (Edelman and Koprowski 2007) and 159 predicts that huddling will result in greater energy savings in larger than small groups 160 (Scantlebury et warm up (i.e. sun basking) on emergence from the burrow in the morning.…”
Section: Introduction 63mentioning
confidence: 99%